1995
DOI: 10.1055/s-2007-1007272
|View full text |Cite
|
Sign up to set email alerts
|

Malignancies After Liver Transplantation: A Comparative Review

Abstract: With the improved survival of patients after liver transplantation, an increase in the incidence of secondary malignancies has been observed. The use of multiple immunosuppressive drugs has been implicated as a strong contributing factor for this increased susceptibility to malignancy, especially cutaneous cancers and lymphoproliferative diseases. With a longer follow-up, we may expect to see a wider variety of malignancies after liver transplantation, probably similar to what we have observed in renal transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
1
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 0 publications
4
12
1
3
Order By: Relevance
“…15 Whether or not the cancers commonly observed in the general population (i.e., carcinomas of the lung, breast, prostate, and colon) occur at higher incidence in the transplant population is controversial. 4,12 Our findings in liver transplant patients concur with those of Penn, 4 who reported that the incidence of these tumors is not increased after transplant. However, early reports from the Cincinnati Tumor Registry did suggest that common tumors tended to occur in transplant recipients at an earlier age than in the general population (i.e., at a mean age of 41 years).…”
Section: Discussionsupporting
confidence: 91%
“…15 Whether or not the cancers commonly observed in the general population (i.e., carcinomas of the lung, breast, prostate, and colon) occur at higher incidence in the transplant population is controversial. 4,12 Our findings in liver transplant patients concur with those of Penn, 4 who reported that the incidence of these tumors is not increased after transplant. However, early reports from the Cincinnati Tumor Registry did suggest that common tumors tended to occur in transplant recipients at an earlier age than in the general population (i.e., at a mean age of 41 years).…”
Section: Discussionsupporting
confidence: 91%
“…This has been reported in renal, 1 bone marrow, 2 heart, 3 and liver [4][5][6][7][8] transplant recipients and is related to an increased number of nonmelanoma skin cancers 9 and lymphomas. 5,6 Although immunosuppression has a central role in the development of cancer, the risk for de novo tumor after orthotopic liver transplantation (OLT) has not been well studied. The aim of our study is to identify risk factors associated with de novo malignancies in liver transplant recipients.…”
mentioning
confidence: 99%
“…There is considerable evidence that a higher cancer rate accompanies transplantation surgery after the introduction of immunosuppressive methods [15]. Data showing increased incidence of neoplasms following therapeutic immunosuppression exist for lung carcinoma [62], lymphoma [63][64][65], bladder tumors [66] and mixed tumors [9,[67][68][69][70][71][72]. Although some patients who develop de novo malignancies have readily treatable in situ carcinomas of the cervix, low-grade skin tumors or in situ carcinomas of the vulva and perineum, these data deserve increased attention.…”
Section: Incidence Of Malignancies and Missing History Of Fevermentioning
confidence: 99%